The Influence of Mnemonic Pictures and Students’ Attitudes toward the Students’ Writing Achievement of the Eighth Grade Students of SMP PGRI 1 Palembang - Etty Pratiwi (ELTE Journal (English Languange Teaching and Education), 2014)
ABSTRACT The research investigated the Influence of Mnemonic Pictures and Students’ Attitude toward the Students’ Writing Achievement of the Eighth Grade Students of SMP PGRI 1 Palembang. The problems of the study were found that: (1) there was a significant difference in average of writing achievement between the students who were in positive attitude after being taught using mnemonic pictures strategy and those who were taught using conventional strategy, (2) there was a significant difference in average of writing achievement between the students who were in negative attitude after being taught using mnemonic pictures strategy and those who were taught using conventional strategy, (3) there was a significant difference in average of writing achievement between the students who were in positive and negative attitude after being taught using mnemonic pictures strategy, (4) there was a significant difference in average of writing achievement between the students who were in positive and negative attitude after being taught using conventional strategy, (5) there was an interaction effect of mnemonic pictures strategy and attitude on the students’ writing achievement. The population of the study was the eighth grade students of SMP PGRI Palembang in academic year of 2013/2014 consisting 342 students. The 96 students were taken as a sample by using two stage random sampling. To collect the data the writer used questionnaire to get the students’ attitudes and writing test to get the information about students’ writing achievement in descriptive paragraph. In carrying out the research, the writer used a factorial design. In analyzing the data, the writer used t-test and two ways ANOVA. Keywords: Mnemonic Pictures, Attitude, and Writing Achievement